Implementasi Aplikasi Tabungan Ibu di Posbindu Pesanggrahan, Jakarta Selatan - Retno Fuji Oktaviani; Rinny Meidiyustiani; Imelda; Ravindra Safitra Hidayat; Hakam Ali Niazi; Indah Rahayu Lestari (Universitas Lancang Kuning, 2022)
Housewives play an important role in managing family finances. In managing finances, you must have a clear and accurate monthly budget. This budget must then be adhered to so that finances are really under control. Mothers can make it in writing in a book, or electronically. Currently, the use of gadgets is almost never out of hand because it is considered a source of information that can be accessed anytime and anywhere. Problems of housewives in general, namely: 1). There is no household budget; 2). Uncontrolled spending; 3). Not making a long term plan; 4). Haste in investing. This activity is carried out with the stages of problem identification, analysis of problem solving and solutions, making materials, implementation, evaluation and mentoring. Improving the ability of housewives to manage family finances by using the Android-based Mother's Savings application is considered very effective and efficient. The results of this activity enable housewives to increase their ability to manage finances, improve family welfare, and improve their ability to use information technology.